2022
DOI: 10.1101/2022.08.13.503856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urotensin II-Related Peptides, Urp1 and Urp2, Control Zebrafish Spine Morphology

Abstract: The spine provides structure and support to the body, yet how it develops its characteristic morphology as the organism grows is little understood. This is underscored by the commonality of conditions in which the spine curves abnormally such as scoliosis, kyphosis and lordosis. Understanding the origin of such spinal curves has been challenging in part due to the lack of appropriate animal models. Recently, zebrafish have emerged as promising tools with which to understand the origin of spinal curves. Using z… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Segmentation of individual sh and generation of .DCM les can also be performed manually. A protocol for this described in [14].…”
Section: Analyze Scans Using Fishcut (Fig 8)mentioning
confidence: 99%
See 1 more Smart Citation
“…Segmentation of individual sh and generation of .DCM les can also be performed manually. A protocol for this described in [14].…”
Section: Analyze Scans Using Fishcut (Fig 8)mentioning
confidence: 99%
“…There is also free, open-source software (e.g., 3D Slicer) for this purpose. Details on the use of some of these applications for the analysis of bones in zebra sh and small rodents have been described in previously published protocols [14,15]. Second, our discussion of key considerations for microCT scanning and analysis is not meant to be exhaustive as further details can be attained from published resources [6,16].…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish, genetically similar to humans, are ideal subjects for studying scoliosis due to their inherent susceptibility to the condition (19,20). The circulation of cerebrospinal fluid (CSF) is associated with spinal development and can result in zebrafish developing spinal deformities (21)(22)(23). When CSF flows through neurons in contact with CSF(CSF-cNs) in the central canal, these neurons produce the urotensin-related peptides Urp1 and Urp2 (24-26).…”
Section: Urotensin and Its Related Receptorsmentioning
confidence: 99%
“…Reducing these peptides during zebrafish growth causes spinal deformities similar to human spinal dysplasia (27,28). Bearce et al found that zebrafish lacking Uts2r3 have scoliosis in adulthood; and that Uts2r3, as a receptor of the urotensin family, may regulate spinal morphology (21). Research on Chinese Han patients with AIS has additionally verified a substantial correlation between UTS2R gene mutation and AIS (29).…”
Section: Urotensin and Its Related Receptorsmentioning
confidence: 99%
See 1 more Smart Citation